Extended Chebyshev polynomials for solving bounded and unbounded singular integral equations - Alhawamda H.; Eshkuvatov Z.K.; Taib B.M.; Ibrahim R.I. (Institute of Physics Publishing, 2024)
Indexed by Scopus/ERA